2004
DOI: 10.1074/jbc.m409034200
|View full text |Cite
|
Sign up to set email alerts
|

AAA ATPase p97/Valosin-containing Protein Interacts with gp78, a Ubiquitin Ligase for Endoplasmic Reticulum-associated Degradation

Abstract: Endoplasmic reticulum-associated degradation (ERAD)is a protein quality control mechanism that eliminates unwanted proteins from the endoplasmic reticulum (ER) through a ubiquitin-dependent proteasomal degradation pathway. gp78 is a previously described ER membrane-anchored ubiquitin ligase (E3) involved in ubiquitination of ER proteins. AAA ATPase (ATPase associated with various cellular activities) p97/valosincontaining protein (VCP) subsequently dislodges the ubiquitinated proteins from the ER and chaperone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
194
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(207 citation statements)
references
References 50 publications
12
194
0
1
Order By: Relevance
“…Similarly, a truncation in which the G2BR is interrupted (595) stabilized gp78. A truncation that retained E2 binding (611) but lost the reported binding of gp78 to p97 (34) (Fig. 10, which is published as supporting information on the PNAS web site) was indistinguishable from WT gp78 in its own degradation (Fig.…”
Section: The G2br and Cue Domain Are Essential For Erad Function Of Gmentioning
confidence: 99%
“…Similarly, a truncation in which the G2BR is interrupted (595) stabilized gp78. A truncation that retained E2 binding (611) but lost the reported binding of gp78 to p97 (34) (Fig. 10, which is published as supporting information on the PNAS web site) was indistinguishable from WT gp78 in its own degradation (Fig.…”
Section: The G2br and Cue Domain Are Essential For Erad Function Of Gmentioning
confidence: 99%
“…Similar binding was also observed for Rfm gp78-Myc (data not shown). Notably, p97/VCP, which cooperates with gp78 in ERAD (Zhong et al, 2004;Ballar et al, 2006), coimmunoprecipitated with CFTR⌬F508 when gp78-Myc was expressed in cells (Supplemental Figure 2). These results indicated that gp78 associates with CFTR⌬F508 and that it recruits p97 to CFTR⌬F508 complexes.…”
Section: Gp78 Is Involved In Erad Of Cftr⌬f508mentioning
confidence: 99%
“…The association of gp78 with CFTR⌬F508 was mediated by its intrinsic CUE domain, which also has ubiquitin binding activity (Supplemental Figure 4; Zhong et al, 2004;Chen et al, 2006). To determine whether the ubiquitin binding region of the CUE domain overlapped the CFTR⌬F508 binding region, we generated a gp78 mutant in which the ubiquitin binding site in the CUE domain, MFP (amino acids 463-465), was mutated to AAR.…”
Section: The Cue Domain Of Gp78 Is Required For Cftr⌬f508 Bindingmentioning
confidence: 99%
“…All proteins had been previously linked to malignancies and are involved in cellular processes like cell growth (RING finger protein and protein kinase C), regulation of the biological homeostasis including haematopoiesis and immunity (G-protein-coupled receptors), apoptosis (VCP) and processes related to cell division (Malate dehydrogenase). 9,11,[33][34][35] Since quantitative 2-DE was not performed, our results only indicate that these proteins are more frequently present in the average proteome of one responder group. This does not exclude that the respective protein will not be expressed in patients belonging to the other responder group, because proteins with a low expression level, for example, might accidentally escape software recognition.…”
Section: Discussionmentioning
confidence: 79%
“…40 Interaction of ubiquitin with the UT3 domain of the Ufd1 enhances VCPpolyubiquitin binding. 33 Furthermore, it regulates TNF-induced apoptosis and NFkB activation via IkBa degradation. 14 Thus, increased VCP expression in PPR could lead to a decreased apoptosis of leukaemic blasts.…”
Section: Discussionmentioning
confidence: 99%